2020
DOI: 10.1055/s-0040-1715465
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Health Outcomes and Quality of Life after Peripartum Hysterectomy for Placenta Accreta Spectrum

Abstract: Objective Short-term morbidity of placenta accreta spectrum (PAS) is well described, but few data are available regarding long-term outcomes and quality of life. We aimed to evaluate patient-reported outcomes after hysterectomy for PAS. Study Design This is a prospective cohort study of women with risk factors for PAS who were enrolled antenatally. Exposed women were defined as those who underwent cesarean hysterectomy due to PAS. Unexposed women were those with three or more prior cesareans or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
0
25
0
2
Order By: Relevance
“…A randomised trial to answer this question is unlikely. Furthermore, recent data suggest significant patient-reported anxiety, grief, and depression in the setting of PAS [16]. While not studied in the present manuscript, delayed hysterectomy may prolong the risk of a patient's psychological experience with PAS and must be considered.…”
Section: Discussionmentioning
confidence: 83%
“…A randomised trial to answer this question is unlikely. Furthermore, recent data suggest significant patient-reported anxiety, grief, and depression in the setting of PAS [16]. While not studied in the present manuscript, delayed hysterectomy may prolong the risk of a patient's psychological experience with PAS and must be considered.…”
Section: Discussionmentioning
confidence: 83%
“…A prospective cohort study among women with MAP and who underwent caesarean hysterectomy at Utah revealed that ongoing decreased QOL and long-term health issues for up to 3 years following surgery than those undergoing LSCS for other indications [ 32 ]. At 36 months, women with MAP who underwent PPH were more likely to report grief, depression, anxiety, and additional surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased quality of life was also reported at 12 and 36 months post-hysterectomy in the PAS group. 1 The present study at assessing sexuality after hysterectomy using the Female Sexual Function Index (FSFI) showed that Total FSFI score was 19.4 ± 3.6 (median 19.8) and for the domains: 3.2 ± 0.9 (desire); 3.2 ± 0.9 (arousal); 3.1 ± 0.6 (lubrication); 3.1 ± 0.7 (orgasm); 3.5 ± 1.1 (satisfaction) and 3.2 ± 1.2 (pain/dyspareunia). All women displayed sexual dysfunction (total FSFI score ≤ 26.55).…”
Section: Discussionmentioning
confidence: 99%
“…When this condition is diagnosed antenatally and women are referred to specialist centres for delivery, the outcome improves signifi cantly. 1 In women with a fi nal diagnosis of placenta increta or percreta, the antenatal diagnosis is associated with reduced bleeding rates and reduced need for blood transfusions, possibly because women diagnosed antenatally are more likely to have preventive therapy for bleeding, and are less likely to attempt to remove their placenta. In addition, more than half of women with placenta accreta, increta, or percreta underwent hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation